Entrepreneurship Orientation, Process Innovation, and Knowledge Management on the Competitive Advantages of MSMEs in Surabaya - Hidayati, Nanda (Westscience Press, 2025)
This study aims to analyze the effect of entrepreneurial orientation, process innovation, and knowledge management on the competitive advantage of micro, small, and medium enterprises (MSMEs) in Surabaya. Grounded in the resource-based view, this research adopts a quantitative approach to examine how internal strategic capabilities contribute to MSME competitiveness in a dynamic business environment. Data were collected from 200 MSME owners and managers using a structured questionnaire measured on a five-point Likert scale. The data were analyzed using multiple linear regression with the Statistical Package for the Social Sciences (SPSS) version 25. The results indicate that entrepreneurial orientation, process innovation, and knowledge management each have a positive and significant effect on competitive advantage. Furthermore, the simultaneous test shows that these three variables jointly explain 50.7% of the variance in competitive advantage. The findings suggest that MSMEs with stronger entrepreneurial behavior, continuous process improvement, and effective knowledge utilization are better positioned to achieve sustainable competitive advantage. This study contributes to the MSME literature by providing empirical evidence on the integrated role of entrepreneurship, innovation, and knowledge management, while offering practical insights for MSME practitioners and policymakers in strengthening competitiveness.